OPTIMIZATION OF THE RESISTANCE SPOT WELDING PROCESS OF SECC-AF AND SGCC GALVANIZED STEEL SHEET USING THE TAGUCHI METHOD - Sukarman Sukarman; Amri Abdulah; Apang Djafar Shieddieque; Nana Rahdiana; Khoirudin Khoirudin (Universitas Mercu Buana, 2021)
This article present the optimization work describes out to joint the dissimilar galvanized steel of SECC-AF (JIS G 3313) and SGCC (JIS G 3302) material. A zinc coating on the surfaces of the galvanized steel sheets will decrease the weldability characteristic of the material. This study used dissimilar galvanised steel sheets to obtain the highest tensile shear strength from the specified resistance spot welding. This research used the Taguchi method with 4-variables and mixed-experimental levels. The mixed-experimental level, namely 2-experimental levels for the first variable and 3-experimental levels for other variables. The highest tensile shear strength was achieved in 5282.13 N. This condition is achieved at a squeezed time of 20 cycles, 27 kA-welding currents, welding time of 0.5 seconds, and holding time of 18 cycles. The S/N ratio analysis has shown the welding current had the most significant effect, followed by welding time, squeeze time, and holding time. The delta values of S/N ratio were 0.79, 0.64, 0.26 and 0.07, respectively. The ANOVA analysis has shown that the P-value of welding current and welding time is 0.006 (0.6%) and 0.015 (1.5%), respectively. This result is expected for optimizing resistance spot welding quality in other materials or significant aspects.